Bird Diversity and Its Relationship with Habitat Characteristics in High Andean Peatbogs - Josens, Maria Laura (2017)
High Andean peatbogs are key functional wetlands in the dry Puna region and essential in conserving local biodiversity, including bird communities. We surveyed the bird communities of 18 peatbogs in the Argentinean Puna (Salta and Catamarca Provinces) to describe their species composition, their patterns of species richness and diversity; and their relationship to landscape features and local environmental variables. In total, we registered 60 species belonging to 21 families during summer 2014-2015. Species richness ranged from six to 20 species per peatbog. The Bright-rumped Yellow-finch Sicalis uropygialis, Ash-breasted Sierra Finch Phrygilus plebejus, Golden-spotted Ground Dove Metriopelia aymara and Puna Miner Geositta punensis were the most abundant representative species. The change in bird species composition among peatbogs showed a nested structure. The present study is the first one made for the avifauna of peatbogs of the Argentinean Puna and shows that the peatbogs with more irregular forms and more interconnected with other wetlands support more abundance and diversity of birds.